2008
DOI: 10.1387/ijdb.072347zp
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of paternal DNA in the late mouse zygote is not essential for development

Abstract: Global demethylation of DNA which marks the onset of development occurs asynchronously in the mouse; paternal DNA is demethylated at the the zygote stage, whereas maternal DNA is demethylated later in development. The biological function of such asymmetry and its underlying mechanisms are currently unknown. To test the hypothesis that the early demethylation of male DNA may be associated with protamine-histone exchange, we ,used round spermatids, whose DNA is still associated with histones, for artificial fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…In this regard it has been shown that when round spermatids are injected into the mouse oocytes, the level of demethylation was lower in male chromatin of round spermatid when compared with normal sperm. Consistent with the above the DNA methylation level was higher in round spermatid than the normal sperm [Polanski et al 2007]. After fertilization, as the replacement of the protamines occurs with histones, bare DNA is probably exposed to demethylation elements.…”
Section: Discussionsupporting
confidence: 64%
“…In this regard it has been shown that when round spermatids are injected into the mouse oocytes, the level of demethylation was lower in male chromatin of round spermatid when compared with normal sperm. Consistent with the above the DNA methylation level was higher in round spermatid than the normal sperm [Polanski et al 2007]. After fertilization, as the replacement of the protamines occurs with histones, bare DNA is probably exposed to demethylation elements.…”
Section: Discussionsupporting
confidence: 64%
“…Otherwise, the presence of some zygotes showing RM<0.4 indicates that the bovine paternal genome can undergo severe genome-wide demethylation under certain circumstances. On the other hand, this is the first study to report pronuclear-stage zygotes showing RM≥1.0; such RM values have been reported in mouse zygotes produced by ICSI and round spermatid injection [48]. The appearance of such zygotes may be due to failure of the oocytes to actively demethylate the paternal genome, as paternal genome has been referred to be relatively hypermethylated than maternal genome in the mouse [49,50].…”
Section: Discussionmentioning
confidence: 71%
“…These hypotheses may be supported by some findings as demethylation of multiple male pronuclei occurred in polyspermic fertilized mouse and human zygotes, while maternal genome in parthenogenetic, gynogenetic or triploid digynic zygotes did not demethylate [15,35]. In addition, bovine oocytes fail to actively demethylate the somatic cell nucleus [14] and abnormal pattern of paternal genome active demethylation was observed after ROSI in mouse [36][37][38]. However, active demethylation was noticed in bovine somatic cell nuclear-transferred zygotes [17].…”
Section: How the Maternal Genome Escape The Active Demethylation Procmentioning
confidence: 90%
“…Neither IVF nor ICSI protocol affected the dynamics of the active demethylation in the mouse [60], but ROSI protocol induced some abnormal dynamics such as insufficient demethylation level and occurrence of re-methylation [36][37][38]. So, it was supposed that the properties of paternal gamete may affect the efficiency of the active demethylation process [57].…”
Section: Effect Of In Vitro Embryo Production On Active Demethylationmentioning
confidence: 99%